2020
DOI: 10.1177/2050313x20945843
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic dilemma – sinonasal organizing hematoma

Abstract: Sinonasal organizing hematomas are benign lesions often mistaken for malignancy due to their aggressive appearance on diagnostic imaging and endoscopic findings that favor advanced disease. The destructive nature of this pathology paired with the rarity of the presentation often results in diagnostic deception that may escalate intervention planning and affect discussion of prognosis with patients. Herein, we present a case of a 56-year-old male with left-sided nasal obstruction and daily epistaxis, where comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Imaging findings of OH are internally heterogeneous, reflecting pathological bleeding and fibrous changes [12] , [13] , [14] , [15] . In typical cases, T1-weighted MRI shows heterogenous intensity and T2-weighted MRI contains high-intensity and hypointense peripheral rim [ 1 , 2 , 4 , 6 , 14 , [16] , [17] , [18] ] and, as in our case, helped for the diagnosis of OH [17] . Previous studies reported that the frond-like pattern of contrast enhancement is one of the characteristic imaging findings of OH that helps to differentiate from other simulating lesions [ 13 , 17 ].…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Imaging findings of OH are internally heterogeneous, reflecting pathological bleeding and fibrous changes [12] , [13] , [14] , [15] . In typical cases, T1-weighted MRI shows heterogenous intensity and T2-weighted MRI contains high-intensity and hypointense peripheral rim [ 1 , 2 , 4 , 6 , 14 , [16] , [17] , [18] ] and, as in our case, helped for the diagnosis of OH [17] . Previous studies reported that the frond-like pattern of contrast enhancement is one of the characteristic imaging findings of OH that helps to differentiate from other simulating lesions [ 13 , 17 ].…”
Section: Discussionsupporting
confidence: 62%
“…Organized hematoma can be curative when the lesion is completely removed. However, these tumors can be overtreated or misdiagnosed preoperatively because of the risk of malignancy [1] . Most OHs are derived from the maxillary sinus, but only four detailed reports have been published on OH of the sphenoid sinus [2] , [3] , [4] , [5] .…”
Section: Introductionmentioning
confidence: 99%
“…Sinonasal organized hematoma is a rare condition that may mimic sinonasal neoplasms on imaging due to its round morphology, locally aggressive nature, and heterogeneous enhancement. The maxillary sinus is the most commonly reported site of involvement [2] , [3] , [4] . Symptoms usually result from hematoma expansion causing displacement and destruction of loco-regional structures leading to epistaxis, facial pain, nasal congestion, and headache [5] .…”
Section: Discussionmentioning
confidence: 99%
“…Correct pre-operative diagnosis is challenging because the symptoms and imaging findings are relatively nonspecific [2,4,14,15]. They are often mistaken as malignancies due to their aggressive clinical appearance and diagnostic imaging findings that favor advanced disease [16,17]. CT findings of sinonasal organized hematomas include expansile mass with heterogenous patchy enhancement in post-contrast images causing adjacent bony changes [2,5,18,19].…”
Section: Discussionmentioning
confidence: 99%